Expert Judgment Regarding ICT in EFL Reading Comprehension Material - Hijril Ismail; Asbah Asbah (Linguistics and ELT Journal, 2021)
Information communication technology is a tool for facilitating the teaching and learning process carried out by manipulating, processing, transferring information between media and managing especially in EFL reading comprehension learning. The purpose of the study is to gain depth information on experts’ judgment to the ICT in EFL reading comprehension material applied to students of English Education Program Universitas Muhammadiyah Mataram. The method applied is qualitative research. The participants involved are three experts namely an English material expert, a learning expert, and an ICT expert. The data were gathered through a questionnaire.  Data analysis was used statistically to obtain the average rating, while the experts’ notes were analyzed descriptively.  The research findings on experts’ judgment presented that the material assessed has already in the high categories or high level of feasibility. It can be shown from the assessment undertaken by an English material expert whose average is 4.0, a learning expert whose average is 4.2, and an information communication material expert whose average is 4.1.